ALIH KODE DAN CAMPUR KODE PADA PEMBELAJARAN BAHASA INDONESIA SEKOLAH MENEGAH DI KOTA SERANG - Erwin Salpa Riansi (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
This research was talk about the problems of mixing code that conducted by teachers and students on teaching Indonesian Language in High School of Kota Serang – Banten. This research found that problems of mixing code. The formal situation could be effected problems of mixing code. The first problem effected by the tearchers that lacks of vocabulary of Indonesian Language. The second promblem was social between teachers and students that made problems of mixing code. Therefore, the third problem from used daily language especially Jawa Serang language could be effected problems of mixing code.